ANALISIS FAKTOR-FAKTOR EKSTERN YANG MEMPENGARUHI KESULITAN BELAJAR PADA PEMBELAJARAN IPS SISWA KELAS V SDN SE-GUGUS I KECAMATAN TAMPAN KOTA PEKANBARU - Ristamala Sari; Hendri Marhadi; Zariul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research motivated by the lowest result of students school grade V in group 1 sub tampan district pekanbaru city in social learning that caused by learning enviroment, inadequate of book package, how to teach teachers, lack of attention from parents and ect. Problems in this subjects made students low so that is caused learning result not appropriate with the expected. This reseach used quantitive descriptive method which aim to know what the extern factors are more dominant affect to difficulties in social learning students school grade V in group 1 sub tampan district pekanbaru city. This research subject consist of 60 students. The retrieve data used questionnaire technique. From this result research was more dominant is parents do not fair with percentage 7,4%. from playmate indicator with percentage 5,6%. This indicates that that externs factors that dominant affect the learning difficulties into the social science learning class V cluster 1 Tampan District, Pekanbaru City is the parental factor of favoritism.Key Words: Analysis, Extern Factors, Difficulty Learning, Social Learning.